1995
DOI: 10.1111/j.1443-1661.1995.tb00388.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Biliary Pressure on Antibiotic Excretion into Bile

Abstract: Biliary obstruction has been recognized to inhibit excretion of antibiotics into bile. In the present study, using cefpirome sulfate (CPR), we sought to determine the effect of biliary pressure on antibiotic transfer into bile in patients undergoing endoscopic retrograde cholangiopancreatography (ERCP). Thirty‐six patients with a variety of biliopancreatic diseases (free of renal disease or hypoproteinemia) received a single intravenous dose of CPR (1 g) prior to ERCP. Under fluoroscopy a diagnostic catheter w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Several investigators reported a discrepancy in biliary secretion of systemically administered antibiotics in the obstructed and non‐obstructed bile both in animal models 15 and in humans 8, 9, 16 . Ciprofloxacin appears to play a particularly different role in which it is secreted efficiently into the bile even under obstructive conditions with penetration ratios of 26–88% 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators reported a discrepancy in biliary secretion of systemically administered antibiotics in the obstructed and non‐obstructed bile both in animal models 15 and in humans 8, 9, 16 . Ciprofloxacin appears to play a particularly different role in which it is secreted efficiently into the bile even under obstructive conditions with penetration ratios of 26–88% 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic antibiotics are usually given, but antibiotic penetration into undrained segments may not be sufficient 20 . MRCP is a non‐invasive means of demonstrating biliary ductal strictures with sensitivity and specificity comparable with endoscopic cholangiography, and renders it possible to evaluate communication and dissociation of intrahepatic bile duct segments 21 .…”
Section: Unilateral or Bilateral Hepatic Drainage For Malignant Hilarmentioning
confidence: 99%